Searching Effective Leader to Improve SME Performance: A Literature Review of Leadership Style - Abdu Alifah; Anggraini Sukmawati (Management Institute Faculty of Economics Universitas Andalas, 2021)
Empirically, previous studies found effective leadership style is critically important in improving small and medium enterprises (SME) performance in both developing and developed countries. However, many SME leaders face some problems related to leadership style due to the lack of understanding of which leadership style is appropriate. Hence, this study attempted to review various leadership styles associated with SME performance and variables that possibly mediate-moderate in-betweens. We explore in-depth 46 empirical research articles related to the leadership style and SME performance published between 2012-2021 through various reputable journal indexing sites. We found and categorized six different leadership styles that effectively improve SME performance containing transformational-transactional, entrepreneurial, sustainable, strategic, servant, as well as ethical and Islamic leadership. Among all the above leadership styles, transformational and entrepreneurial leadership are the most studied and empirically found effective in improving overall SME performance. Limitations and directions for future research are discussed further